Conhecimento e atitudes do enfermeiro sobre dor em neonatos - Freitas, Záira Moura da Paixão (2010)
Pain is responsible for physiological changes and impairment on the neurological development of the newborn, whereas it is difficult for the health professionals to evaluate and measure it. To verify the knowledge of nurses about newborn s pain evaluation and management admitted at a Neonatal Intensive Care Unit (NICU) in a public maternity in Aracaju-Se and to compare the knowledge about pain before and after elucidation about the use of the Neonatal Infant Pain Scale (NIPS). This study is a research action, under quantitative approach. A questionnaire was applied to assess nurse s demographic and professional data, knowledge about pain, assistance given to a newborn with pain and strategies adopted for pain prevention and treatment. The follow up of the professional was also performed, so she could evaluate the presence or not of pain on newborn, being undergone to a painful procedure or not, through the fulfillment of the NIPS scale. Data collection occurred in the period from December of 2008 to August of 2009. Thirty nurses aging between 23 and 46 years old (32,9; ± 6,9) were enrolled in the study. All participants came to the conclusion that the newborn feels pain, both behavioral and physiological parameters were used to evaluate it. Twenty one nurses (70%) had no knowledge about any scale to evaluate newborn s pain, while only nine (30%) knew someone, at least one and maximum of three scales. During the first and second evaluations with the use of the NIPS, however without elucidation of parameters so it could be interpreted, revealed a frequency of 18 (30%) newborns diagnosed with pain and 42 (70%) infants diagnosed with no pain. The third and fourth evaluations, after elucidation about NIPS, revealed an increased number of infants diagnosed with pain (n= 39, 65%) and a decreased number of newborns diagnosed with no pain (n= 21, 35%). The nurses came to the conclusion that the newborn feels pain, both behavioral and physiological parameters were used to evaluate it, but demonstrated little knowledge about the use of pain scale. The explanation made easy and influenced positively for the evaluation and diagnosis of pain.